Endoscopic endonasal transsphenoidal approach for resection of a coexistent pituitary macroadenoma and a tuberculum sellae meningioma - Mahvash, Mehran; Igressa, Ahadi; Pechlivanis, Ioannis; Weber, Friedrich; Charalampaki, Patra (Asian Journal of Neurosurgery, 2014)
The coexistence of a pituitary macroadenoma and a tuberculum sellae meningioma is very rare. This article demonstrates the surgical technique of the simultaneous resection of a pituitary macroadenoma and a tuberculum sellae meningioma using an endoscopic, endonasal, biportal, transsphenoidal approach. A 36-year-old woman presented with frontal headache and extended visual field loss of the right eye. She underwent cranial magnetic resonance imaging (MRI) revealing a 2 × 2× 2.5 mm contrast-enhancing intrasellar and suprasellar lesion with compression of the optic chiasma. The coexistence of a pituitary macroadenoma and meningioma was suggested. A biportal endoscopic endonasal transsphenoidal approach was performed to remove both lesions. The histological results confirmed the coexistence of the pituitary macroadenoma and meningioma, World Health Organization (WHO) grade I. The endoscopic, endonasal, transsphenoidal approach is a safe and reliable minimal invasive surgical alternative for resection of the intra-, supra- and parasellar lesions, avoiding additional craniotomy.
Keywords: Coexistence; endoscopic resection; pituitary adenoma; tuberculum sellae meningioma